RESULTS OF INVESTIGATIONS ON THERMAL CHARACTERISTICS OF AIR HEATER BUNDLE MADE OF BIMETALLIC FINNED TUBES - V. B. Kuntysh; V. V. Dudarev; A. B. Sukhotsky; V. I. Volodin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a scheme and description of a new aerodynamic stand that has a 300x300 mm cross-section operating channel. The stand is used for studying thermal and aerodynamic characteristics of bundles made of finned tubes of actual dimensions in crossflow. The paper provides results of an exploratory test pertaining to heat transfer and resistance of four row staggered bundle made of tubes with aluminium spiral fins having outside diameter of 26 mm which are used in the systems of ventilation, air-conditioning and heating of buildings and also in transport heat exchangers.